Pengaruh Sertifikasi Halal, Viral Marketing Dan Brand Image Terhadap Keputusan Pembelian Produk Mixue Kota Malang (Studi Pada Konsumen Mixue Tlogomas ) - Antaseni, Fiona; Basalamah, Muhammad Ridwan; Rahmawati, Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study looked at how brand perception, viral marketing, and halal certification affected consumers' decisions to buy Tlogomas ice cream and tea mixue goods. This study employs a quantitative approach with non-probability sampling approaches, and the primary data source is consumers who have purchased Tlogomas ice cream and tea mixes. Data are gathered using a likert scale questionnaire. The sample calculation in this study used the Malhotra formula which produced 75 respondents. The data analysis used is descriptive analysis, instrument testing, classical assumptions, multiple linear regression analysis and hypothesis testing using SPSS 25 for Windows. The results of this research show that halal certification, viral marketing and brand image simultaneously and partially influence the decision to purchase Tlogomas ice cream & tea mixue products. Keywords :Halal Certification, Viral Marketing, Brand Image And Purchasing Decisions